Biotic and Abiotic Factors That Condition the Bioremediation Byin Grounds Contaminated By Hydrocarbons - Gómez Romero, Sara Esmeralda; Gutiérrez Bustos, Diana Carolina; Hernández Marín, Ana María; Hernández Rodríguez, Cindy Zulay; Losada Casallas, Maríana; Mantilla Vargas, Paula Cecilia (Nova, 2019)
The bioremediation of hydrocarbons process, polluting agents of the ground, carried out by Pseudomonas sp. is in conditioned by biotic and abiotic factors, like the nutrients, breathing, pH, humidity and temperatureof the microorganism, which, when modified, limit or favor the metabolic capacity of the bacterium andits adaptability with the shift of position of fatty acids of the cellular membrane. Ground bioremediationhas demonstrated to be an effective technology for the treatment of the contamination by petroleum,because the majority of the crude components and its refined products are biodegradable. This revisionis to describe the biotic and abiotic conditions needed by the Pseudomonas sp. in order to carry out a, suitable process of bioremediation, considering the characteristics and properties of the bacterium. El proceso de biorremediación de hidrocarburos, contaminantes del suelo, llevado a cabo por Pseudomonas sp. está condicionado por factores bióticos y abióticos como los nutrientes, respiración, pH, humedad y temperatura propios del microorganismo, los cuales al ser modificados limitan o favorecen la capacidad metabólica de la bacteria y su adaptabilidad con el cambio de posición de los ácidos grasos de la membrana celular. La biorremediación de suelos ha demostrado ser una tecnología eficaz para el tratamiento de la contaminación por petróleo, debido a que gran parte de los componentes del crudo y sus productos refinados son biodegradables. La presente revisión tiene por objetivo describir las condiciones bióticas y abióticas que necesitan las Pseudomonas para llevar a cabo un adecuado proceso de biorremediación, teniendo en cuenta las características y propiedades de la bacteria.